Pengembangan Organisasi Menggunakan Open System Model - Mohammad Risqi; Luqman Tifa Perwira (Psyche 165 Journal, 2021)
Pt. PN is a company engaged in coal mining contractors. One of the vision &mission of PT. PN is becoming a global top 8 company that has excellence in all fields. Business expansion is one of the company's agenda to become an excellent mining company in Indonesia. This research was conducted to identify and map problems in PT PN by using open system model diagnostic method and data collection with qualitative method. The results showed that there are problems in the HRM system, not optimal HRM system because the development program has not been optimal, so it has an impact on employee competence, competency problems then impact on employee readiness on the business expansion agenda. Mentoring program intervention at the deputy project manager level aims to assist the company in carrying out the development process in the company. The intervention of this mentoring program also supports the company's mission in improving the quality of human resources and preparing competent cadres for organizational sustainability.